Effect of microbes on wound healing / Muhammad Yusri Mohd Yusoff - Mohd Yusoff, Muhammad Yusri (2009)
This study investigated the effects of type and load of microbes on wound healing status of rat skin. P. aeruginosa and S.aureus, the most common wound infection pathogen, were used as microbes of interest. The findings indicated that the use of P .aeruginosa resulted in slower wound healing of rat skin than that of S. aureus. High microbial load gave rise to a slower wound healing than low microbial load.